Anxiety among individuals with visual vertigo and vestibulopathy. (6th November 2015) - Zur, Oz; Schoen, Gila; Dickstein, Ruth; Feldman, Jacob; Berner, Yitshal; Dannenbaum, Elizabeth; Fung, Joyce
Abstract: Purpose : Visual vertigo (VV) is a type of dizziness triggered by visual stimuli. Despite a high incidence, its relationship with anxiety is not well-defined or understood. This study evaluated anxiety levels in subjects with VV compared to vestibulopathic subjects without VV and healthy individuals. Methods : A cross-sectional study to evaluate anxiety among individuals with VV was conducted twice. The first study included 72 participants (66 to 83 years of age) from senior residential centers. The second included 31 participants from a vestibular rehabilitation program (age range 35–82 years). Study 1 also used the Activities-Specific Balance Confidence (ABC) scale and study 2 the Dizziness Handicap Inventory (DHI). Results : Subjects were classified as VV positive (27 in study 1, 10 in study 2) or vestibulopathic without VV (30 in study 1, 11 in study 2) based on Head Impulse or Dynamic Visual Acuity Tests and the Dizziness Questionnaire. The remaining were age-matched healthy controls. The outcome of each study demonstrated significantly higher anxiety levels ( p =  0.0001) in the VV group compared to the other groups. The results of the ABC test demonstrated that subjects in the VV group had significantly lower self-confidence ( p =  0.001) than those in the Vest and Cont groups and performed fewer balance-related activities of daily life. DHI results showed that VV group expressed higher ( p  < 0.001) mean scores for self-perceived feelings of dizziness and imbalance (54%), compared to the Vest (9%) and Cont groups (1%). Conclusions : Anxiety related to VV requires special attention when assessing and managing vestibulopathy, regardless of patient age. Implications for Rehabilitation: Anxiety is a characteristic of subjects with visual vertigo (VV) and vestibulopathy. Anxiety in subjects with VV is not related to age. VV should be considered when subjects with anxiety complain of imbalance. Anxiety and vestibulopathy are often interrelated and should be considered in diagnostic evaluations.